(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
نص المشرع السوري في قانون براءات الاختراع في المادتين (39-40) على الترخيص الاجباري وفق حالات متعددة أهمها حالة اخلال المالك بالتزامه في استغلال الاختراع، حيث ناقشنا في هذه الدراسة المقصود بمبدأ الاستغلال والشروط الواجب توافرها في الاستغلال، وحددنا المقصود بالترخيص الاجباري وشروطه والجهة المختصة بمنحه، كما بيّنا الآثار المترتبة على الترخيص الاجباري من خلال بيان حقوق والتزامات كل من المالك والمرخص له، وتطرقنا إلى حالة سكت عنها المشرع السوري المتعلقة بحق المرخص له بتعديل شروط الترخيص الاجباري في حال قيام المالك بمنح تراخيص اتفاقية افضل من الشروط التي يتضمنها الترخيص الاجباري، لذلك قدمنا توصية بإضافة مادة على قانون براءات الاختراع السوري تنص على أنه: ((يمكن للمديرية تعديل قرار منح الرخصة الاجبارية بطلب من المستفيد من الترخيص الاجباري في حال قام مالك البراءة بمنح تراخيص اتفاقية بشروط أفضل للمرخص له اتفاقيا)). The Syrian legislator in the patent law in articles (39-40) provides for compulsory license according to several cases, the most important of which is the owner’s breach of his obligation to utilize the invention. We discussed in this study the meaning of the utilization principle, and the conditions that must be available in the utilization. We have defined the meaning of the compulsory license, its conditions and the competent authority to grant it. We clarified the implications of compulsory licensing through stating the rights and obligations of both the owner and the licensee. We referred to a case not addressed by the Syrian legislator regarding the licensee’s right to modify the conditions of compulsory license in case the owner granted a license agreement better than the conditions included in the compulsory license. We recommended the addition of an article to the Syrian Patent Law stipulating that "the Directorate may amend the decision to grant the compulsory license at the request of the beneficiary of the compulsory license if the patent owner grants an agreement license on better terms to the contractual licensee."